2011
DOI: 10.1249/mss.0b013e31820f8395
|View full text |Cite
|
Sign up to set email alerts
|

Valgus Plus Internal Rotation Moments Increase Anterior Cruciate Ligament Strain More Than Either Alone

Abstract: Combined knee valgus and internal rotation moments increases ACL strain more than either alone. The combination of a valgus and internal rotational moment at magnitudes that occurs in vivo during landing can cause ACL strains that may be high enough to cause ACL rupture. This predicted high ACL strain and the contact force location suggest that combined valgus and internal tibial rotational moments during single-leg landing are relevant to ACL injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
187
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(196 citation statements)
references
References 45 publications
9
187
0
Order By: Relevance
“…In previous investigations, combined rotational stimuli have had a greater impact on ACL strain than rotations in any individual DOF. This has been documented in computational models [50], impact testing [32,40,41], and robotic manipulator-driven articulations [5].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In previous investigations, combined rotational stimuli have had a greater impact on ACL strain than rotations in any individual DOF. This has been documented in computational models [50], impact testing [32,40,41], and robotic manipulator-driven articulations [5].…”
Section: Discussionmentioning
confidence: 91%
“…Because clinical ACL injuries occur within the first 50 msec of contact [29], investigation of ligamentous response to perturbation in initial contact orientations should prove relevant to injury mechanics. The rotational perturbations selected have been identified as contributors to ACL strain [32,40,41,50,52], motions secondarily resisted by the ACL [12], or (in the case of knee abduction) predictors of ACL injury risk [13]. The minor alterations in absolute ACL strain induced by the presently applied rotational stimuli were not found to be different from strain magnitudes recorded at the neutral limb position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that valgus moment at the knee joint does increase ACL strain, but the physiological level of isolated valgus moment observed only in vivo may not be sufficient to rupture the ACL without concomitant damage to the MCL, because coupled tibial external rotation and increasing strain in the MCL prevent proportional increases in ACL strain at higher levels of valgus moment [219]. On the other hand, when valgus moment and tibial internal rotation moment are applied in combination, the two rotational moments can cause levels of ACL strain that may be high enough to cause ACL injury [220]. Furthermore, during landing when the combined maximum valgus moment and tibial internal rotation moments were applied, the peak contact force occurred at the posterior-lateral side of the tibial cartilage in the model that agreed with the bone bruise locations that have often been observed in acute ACL-injured patients examined by MRI.…”
Section: Computational Simulationmentioning
confidence: 99%
“…Previous studies have shown that both knee abduction moments and tibial internal rotation moments strain the ACL and that these moments have an interaction effect at physiologic load levels, creating strains approaching the reported range of ACL rupture [7][8][9][10]. One prospective cohort study has shown that peak knee abduction moment during a drop-jump activity could predict ACL rupture with 73% specificity and 78% sensitivity in a population of 205 female athletes, further implicating increased peak knee abduction moments as a factor in ACL injury risk [11].…”
Section: Introductionmentioning
confidence: 99%